STEM-INTEGRATED PROBLEM-BASED LEARNING WITH LOCAL WISDOM (GONG BULEUH): IMPACT ON STUDENT LEARNING OUTCOMES - Anggrek Adewina Siahaan; Haerul Pathoni; Jules Nurhatmi (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
The purpose of this study is to implement STEM-integrated PBL based on local wisdom (Gong Buleuh) on sound wave materials and analyze its effect on improving student learning outcomes. The method used in this study is quasi-experimental with a non-equivalent control group design. This research involved two classes of XI Science at SMA Negeri 8 Jambi City, each consisting of 30 students. The experimental class used STEM-based integrated PBL based on local wisdom (Gong Buleuh), while the control class used PBL without integration. A pretest and posttest were administered to evaluate students’ learning achievement. After implementation, students in the experimental class demonstrated significantly improved learning outcomes compared to those in the control class. The paired sample t-test showed a significance value of 0.000 and a large effect size (Cohen's d = 7.76). Furthermore, independent sample t-tests showed significant differences between the experimental class and the control class, with a significance value of 0.000 and a large effect size (Cohen's d = 1.78). These results suggest that incorporating local wisdom and STEM approaches into the PBL model can improve student learning outcomes and have high relevance in efforts to improve the quality of physics education in secondary schools.